Analisis Penentuan Lokasi Tempat Pembuangan Akhir Di Kota Tidore Kepulauan - Buyung Faisal; Rudi Latief; Idris Taking (Fakultas Teknik Universitas Bosowa, 2022)
The purpose of this research is to find out locations that have the potential to be used as landfill sites in the City of Tidore Islands with the applicable provisions or have been set